2023
DOI: 10.3390/ma16216940
|View full text |Cite
|
Sign up to set email alerts
|

Surface Engineering of Bioactive Coatings for Improved Stent Hemocompatibility: A Comprehensive Review

Amisha S. Raikar,
Sushma Priya,
Shilpa P. Bhilegaonkar
et al.

Abstract: Cardiovascular diseases continue to be a major contributor to illness and death on a global scale, and the implementation of stents has given rise to a revolutionary transformation in the field of interventional cardiology. The thrombotic and restenosis complications associated with stent implantation pose ongoing challenges. In recent years, bioactive coatings have emerged as a promising strategy to enhance stent hemocompatibility and reduce thrombogenicity. This review article provides an overview of the sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Over the years, the design and material from which stents are made have undergone significant modifications. Systematizing the available types of vascular scaffolds, three groups can be distinguished: metal stents-BMSs (bear metal stents), drug-eluting metal stents [51]-DESs (drug-eluting stents) (Figure 1) [52] and a group of bioresorbable stents-BRSs (bioresorbable stents) [53,54]. Metal stents can be made of thin 316L-grade stainless steel, cobalt-chromium, and platinum-chromium.…”
Section: Stents and Cathetersmentioning
confidence: 99%
“…Over the years, the design and material from which stents are made have undergone significant modifications. Systematizing the available types of vascular scaffolds, three groups can be distinguished: metal stents-BMSs (bear metal stents), drug-eluting metal stents [51]-DESs (drug-eluting stents) (Figure 1) [52] and a group of bioresorbable stents-BRSs (bioresorbable stents) [53,54]. Metal stents can be made of thin 316L-grade stainless steel, cobalt-chromium, and platinum-chromium.…”
Section: Stents and Cathetersmentioning
confidence: 99%
“…The biomolecular coating modified on the surface of biomedical materials is a direct contact site for cell adhesion and growth on the material surface, which has a significant impact on human physiological activities [1][2][3][4][5][6]. Numerous in vivo and in vitro animal experiments have shown that Mg alloy materials modified with functional biomolecular coatings have good biocompatibility, biomechanical compatibility, antibacterial properties, and appropriate corrosion resistance performance [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%